Relação entre desempenho ambiental e desempenho econômico de empresas no Brasil e na Espanha - Alves, José Flávio Vasconcelos (2012)
The damage caused to the environment affect directly the quality of life of people and this will demand of organizations, activities that include the preservation, prevention and recovery of the environment in which they live. Companies that signal an environmentally correct behavior is rewarded with economic benefits and can remain on the market because they are legitimate, or have the endorsement of society to function. For the legitimacy, the company that adopts and signals good environmental practices, have to make investments, which may vary from company to company. Based on the Signaling Theory and the Theory of Legitimacy, this study focuses on companies in Spain and Brazil, considered countries that are published reports of environmental sustainability. This work aims to investigate the relationship between economic performance and environmental performance of companies in Brazil and Spain. And also, the correspondence between the level of environmental performance and environmental impact of the Brazilian and Spanish in the secondary sector. For this task, we carried out a descriptive, quantitative, utilizing the bibliographic and documentary procedures. The sample consisted of 25 Spanish publicly traded companies and 41 publicly traded Brazilian companies in the year of 2010 and 39 publicly traded Brazilian companies in the year of 2009, listed in the list of companies that publish sustainability reports in accordance with the GRI G3 standard model in the year of 2010. The information was collected from the environmental performance of companies in GRI reports 2009 and 2010, by the total environmental investments (EN 30), while the information on the economic performance were extract by financial statements of companies in the years 2009 and 2010 , prepared according to the pattern of international accounting standards (IFRS). Statistical tests involving elaborate Spearman correlation tests and the analysis of correspondence (ANACOR). The results suggest that there is a moderate positive correlation between ROA and environmental investment indicator (EN30/assets) in companies in Brazil. In Spain, there is a strong negative correlation between ROA and environmental investment indicator. Taking into account the attribute of the lag, the positive relationship between the performance was confirmed in Brazil, while in Spain show a null correlation between economic indicators, and a negative correlation with primaries variables. The results of the correspondence analysis between the level of environmental impact of corporate activities and level of environmental performance, suggest that companies with high environmental impact have an average environmental performance analyzing the two countries together.